Adesão bacteriana e formação de biofilme em materiais para implantes dentários - Avila, Erica Dorigatti de [UNESP] (2015)
Dental implant rehabilitation has become a routine procedure to replace missing teeth. Its success depends on proper osseointegration, as well as the lack of inflammation. An important factor contributing to the development of inflammation is the attachment of microorganisms and subsequent development of biofilms on the prosthetic components. This study focused on effect of materials and treatment surfaces on the bacterial adhesion and biofilm formation. We, first, assessed the biofilm formation on machined titanium (Ti) discs treated and untreated with UV photofunctionalization. UV-treatment was performed using a photo-device for 12 minutes. Hydrophobic-to-hydrophilic conversion was confirmed on UV-treated titanium surfaces. Biofilm was formed by incubating the discs in rich medium containing a complex representative saliva-derived oral microbial community. After 3 and 16 hours, the biomass of biofilm and the bacteria profile was analyzed. For other experiments, it was used titanium and zirconia (ZrO2) discs as abutment implants and bovine enamel (BE) as a positive control. Roughness means that topography and energy-free surface analysis were performed prior to applying microbiology biofilms onto materials. Biofilms in single species with Streptococcus mutans (S. mutans), Porphyromonas gingivalis (P. gingivalis) and Fusobacterium nucleatum (F. nucleatum) and multi species with P. gingivalis and F. nucleatum were developed on each samples and quantitatively evaluated by counting forming units (CFU) and qualitatively by confocal microscopy. Also, we analyzed the development of a complex oral biofilm on two different abutments implants surfaces. Quantitatively and qualitatively analysis were performed after 16 and 48 hours of incubation under anaerobic conditions. In relation to first study, the biomass of biofilm formed on UV treated surfaces was significantly... (Complete abstract electronic access below)